PEOPLE’S POLITICAL TRUST TOWARDS LOCAL POLITICIANS IN KHONKAEN PROVINCE - Thattanon, Nipa; Promgun, Suraphon; Meenonthongmahasan, Pruchya (Journal of Graduate MCU KhonKaen Campus, 2021)
The objectives of this research were: 1) to study the level of political trust of the people towards local politicians in Khon Kaen Province; 2) to study the level of performance according to the Four Sangahavatthu Dhammas (Bases of Social Solidarity) of local politicians in Khon Kaen Province; 3) to compare people’s political trust to local politicians in Khon Kaen Province, classified by the samples’ personal factors and performance according to the Four Sangahavatthu Dhammas; 4) to study guidelines for promoting political trust of local politicians in Khon Kaen Province. The samples used in the study consisted of 400 people and 8 key informants in the interviews. The tools for data collection were: questionnaires and interviews. The obtained data analyzed by using a social science program and descriptive content analysis. The research results were as follows: 1) The political trust of the people towards local politicians in Khon Kaen Province, in overall and in each aspect, was statistically rated at a high level. 2)The level of performance in accordance with the Four Sangahavatthu Dhammas of local politicians in Khon Kaen Province, in overall and each aspect, was at a high level. 3) The comparison results showed that people with differences in age, education, monthly income and performance in accordance with the Four Sangahavatthu Dhammas had the political trust in overall differently with the statistical significance level of 0.05; while, those with differences in gender and occupation had the political trust indifferently. 4) The political trust building guidelines are that in the personal aspect, the local politicians should have a vision of local development at present and in the future. In the aspect of policy, clear policies should be set in relations to local problems. In terms of communication, there should have a fast communication method through a variety of channels. In terms of work processes, monitoring and evaluation of the results of operations should be carried out in accordance with the established policies. As for the operation according to the Four Sangahavatthu Dhammas, it should provide assistance to the people by providing what they lack in order to heal their suffering, doing as what is said, sacrificing their own interests for the public and performing the public benefit for the people and society.